Penerapan Teknologi Tepat Guna dalam Mewujudkan Daerah Mandiri dan Berkelanjutan - Muhammad Agil Zuhairi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The application of appropriate technology (TTG) is an innovative approach in realizing independent and sustainable regional development. This technology is designed to meet community needs by considering local social, economic, cultural and environmental conditions. This research aims to explore the basic concepts, roles and factors for the success of implementing TTG in the context of sustainable development. Appropriate technology has an important role in increasing productivity, creating jobs and strengthening regional independence. The success of its implementation is influenced by community participation, government policy support, availability of resources, and technological innovation. TTG contributes to achieving sustainable development goals, such as reducing poverty, providing renewable energy, and inclusive infrastructure development. However, the main obstacles to its implementation include limited skilled human resources, limited funding, and inadequate infrastructure. Therefore, synergy between stakeholders is needed to ensure effective and sustainable implementation of TTG. This research suggests increasing training, using local resources, and supporting policies that support TTG development at the regional level.